2010
DOI: 10.1007/s00432-010-0940-6
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody against hypoxia-inducible factor prolyl hydroxylase-3 is a potential serological marker for renal cell carcinoma

Abstract: The present study suggests that the anti-PHD3 Ab may be a novel serological marker for RCC and the titer may reflect the tumor burden in each individual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The oxygen sensing prolyl hydroxylase family member PHD3 displays high expression levels in ccRCC tumours and derived cell lines [23, 24]. Recent studies have suggested a number of both hydroxylase-dependent and hydroxylase-independent roles for PHD3 also beyond the HIF pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxygen sensing prolyl hydroxylase family member PHD3 displays high expression levels in ccRCC tumours and derived cell lines [23, 24]. Recent studies have suggested a number of both hydroxylase-dependent and hydroxylase-independent roles for PHD3 also beyond the HIF pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, PHD3 has been suggested to function as an activator of fatty acid oxidation via ACC2 [22]. PHD3 overexpression has been seen in many types of cancer, including ccRCC [23, 24]. Importantly, high PHD3 expression serves as a marker for poor prognosis in ccRCC patients [25] as well as in other types of cancer [26].…”
Section: Introductionmentioning
confidence: 99%
“…A study demonstrated that PHD3 mRNA level was increased in different anatomical sites including tongue, mouth floor and tonsils [45]. Increased PHD3 expression under hypoxia enhances cell cycle progression and survival of carcinoma cells [46]. …”
Section: The Function Of Phd3 In Different Cancersmentioning
confidence: 99%
“…found that PHD3 was overexpressed in 21 of the 22 renal cell carcinoma (RCC) specimens through RT-PCR analysis and anti-PHD3 antibody may be a novel serological marker for RCC [47]. PHD3 is mainly overexpressed in RCCs, but rarely in normal tissues and was recognized as a cancer-specific antigen and might be a target in immunotherapy for RCC [48].…”
Section: The Function Of Phd3 In Different Cancersmentioning
confidence: 99%
“…Prolyl hydroxylase-3 (PHD3/ENGL3) is a member of the PHD family, which is involved in the degradation of HIF proteins in cooperation with VHL protein under normoxic conditions. PHD3 was found frequently over-expressed in RCC tissues, with high specificity to cancer samples (Zhao et al, 2006) and its usefulness as a novel tumor antigen for RCC immunotherapy has been recently demonstrated in clinical serum samples from RCC patients (Sato, 2008;Tanaka, 2011). Insulin-like growth factor binding protein 3 (IGFBP3) is one of the most over-expressed genes in ccRCC (Takahashi, 2005;Yao, 2005) and its increased protein expression has been demonstrated in 74% of ccRCCs by IHC and associated with higher Fuhrman nuclear grade (Chuang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%